2014
DOI: 10.2203/dose-response.14-028.mattson
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Oneself Intermittently to Improve Health

Abstract: h Humans and their predecessors evolved in environments where they were challenged intermittently with: 1) food scarcity; 2) the need for aerobic fitness to catch/kill prey and avoid or repel attackers; and 3) exposure to biological toxins present in foodstuffs. Accordingly, cells and organ systems acquired and retained molecular signaling and metabolic pathways through which the environmental challenges enhanced the functionality and resilience of the cells and organisms. Within the past 60 years there has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 130 publications
(122 reference statements)
2
31
0
Order By: Relevance
“…In line with previous publications [26, 27, 28, 29, 69] it can be hypothesized that the health‐ and life‐span extending effects are not necessarily derived from the energy reduction only, but that intermittent exposure to challenges might have an additional health‐promoting effect. Apart from exposure to alternating energy availability in this study the gastrointestinal tract as well as metabolic organs like the liver, were challenged to handle variations in carbohydrate and fat content.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In line with previous publications [26, 27, 28, 29, 69] it can be hypothesized that the health‐ and life‐span extending effects are not necessarily derived from the energy reduction only, but that intermittent exposure to challenges might have an additional health‐promoting effect. Apart from exposure to alternating energy availability in this study the gastrointestinal tract as well as metabolic organs like the liver, were challenged to handle variations in carbohydrate and fat content.…”
Section: Discussionsupporting
confidence: 80%
“…Importantly, increasing evidence points out that the beneficial health effects of (intermittent) CR are not solely caused by reduced body weight 24, 25. Timing and limitation of meal frequency affect the circadian rhythm and might induce a repetitive challenge that most likely will contribute to the health promoting effects 26, 27, 28, 29. We recently reported that an intermittent energy restriction (INT) diet maintains metabolic health and reverses the adverse effects of the moderate‐fat (MF) diet, when provided for 10 months to 9‐week‐old male C57BL/6J mice 30.…”
Section: Introductionmentioning
confidence: 99%
“…CR has been demonstrated to prolong lifespan, preventing many age-associated diseases, and it improves the general health of overweight humans [30]. Mattson and Wan [31] also revealed that CR has an important role in regulating both cardiovascular and brain functions.…”
Section: Caloric Restrictionmentioning
confidence: 99%
“…It has been argued that laboratory diet and conditions allow rodents to become obese (Mattson, 2014), thus accounting for the apparent metabolic benefits of CR. Genetic factors may have an impact on the outcomes of CR.…”
Section: Unraveling the Relationships Among Calorie Restriction Lmentioning
confidence: 99%